Przypisy tłumacza w wybranych słoweńskich przekładach literatury polskiej - Bednarska, Katarzyna; Szafraniec, Kamil (Przekłady Literatur Słowiańskich, 2017)
Translator`s Footnotes in the Chosen Translations of Polish Literature Inspired by the theories of such well recognized scholars as G. Genette ,J. Derrida and E. Skibińska the authors of this paper took a closer look into translators’ comments in Slovene translations of three Polish novels. The analytical part of the paper has been divided into two sections. The first one described the formal characteristics of footnotes. The second one illustrated different cultural, social, and historical contexts of using additional translators` comments. Keywords: Polish literature, Slovenian literature, translator`s footnotes, Translation Studies, peritexts